(untitled) (Jurnal Pembangunan Perikanan dan Agribisnis, 2022)
This research aimed to analyze the effect of capital and employees on the production and income of milkfish ponds business as well as analyze the factor which is more dominant in affecting the production and income of milkfish ponds business. The field data collection was done in July 2019 in Babulu Laut Village. The sampling method used Proportional Stratified Systematic Sampling with the total sample of 32 people. The data analysis method used was multiple linear regression analysis using SPSS version 16. The research results obtained that: (1) capital and employee factors significantly affects the production and income of milkfish ponds business; (2) the dominant factor in affecting the production and income of milkfish ponds is the employee factors. Keywords: Capital, Employee, Production and Income